2022
DOI: 10.1158/1078-0432.ccr-22-0164
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Composition of Commercial Anti-CD19 CAR T Cells Affects In Vivo Expansion and Disease Response in Patients with Large B-cell Lymphoma

Abstract: Background: In clinical trials, the expansion and persistence of CAR-T cells correlate with therapeutic efficacy. However, properties of CAR-T cells that enable their in vivo proliferation have still to be consistently defined and the role of CAR-T bag content has never been investigated in a real life setting. Experimental Design: Residual cells obtained after washing 61 anti-CD19 CAR-T product bags were analysed to identify tisagenlecleucel/Tisa-cel and axicabtagene ciloleucel/Axi-cel phenotypic features ass… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 34 publications
5
20
0
Order By: Relevance
“…Similar findings were reported by Monfrini et al. ( 70 ) who tested 42 patients (33 DLBCL, 8 primary mediastinal B-cell lymphomas and 1 MCL) treated with commercial anti-CD19 CAR-T cells. A unique ddPCR primer-probe assay was developed to quantify CAR vectors on genomic DNA.…”
Section: Ddpcr In Chronic Lymphoid Malignanciessupporting
confidence: 88%
See 1 more Smart Citation
“…Similar findings were reported by Monfrini et al. ( 70 ) who tested 42 patients (33 DLBCL, 8 primary mediastinal B-cell lymphomas and 1 MCL) treated with commercial anti-CD19 CAR-T cells. A unique ddPCR primer-probe assay was developed to quantify CAR vectors on genomic DNA.…”
Section: Ddpcr In Chronic Lymphoid Malignanciessupporting
confidence: 88%
“…These data were independent from the product employed. ddPCR showed a significant correlation with flow cytometry (r=0.95, p <0.0001 by Pearson correlation) with the advantage of detecting residual CAR-T cells in samples with limited cellularity and/or cryopreserved (bag-leftovers, cryopreserved BM, biopsies, cfDNA) ( 70 ). Different assays have been developed for commercial CAR-T cell monitoring.…”
Section: Ddpcr In Chronic Lymphoid Malignanciesmentioning
confidence: 99%
“…Different studies have shown clinical differences between Tisacel and Axicel; nevertheless, scarce information is available regarding the differences in the immunophenotype of CAR-T cells comparing these two products and most studies available are focused on the evaluation of the infusion products (38). With this background, in the current study immunophenotypic characterization of non-modified T cells and CAR-T cells was compared between both products at the time of peak expansion.…”
Section: Discussionmentioning
confidence: 99%
“…The second type is late relapse after achievement of good clinical response following CAR-T cell treatment ( 7 ). Detailed analysis of the input material and the produced CAR-T cells could help identify factors responsible for these types of treatment failures ( 8 10 ).…”
Section: Introductionmentioning
confidence: 99%